Emotionality of Colors: An Implicit Link between Red and Dominance - Mentzel, Stijn V.; Schücker, Linda; Hagemann, Norbert; Strauss, Bernd (Frontiers in Psychology, 2017)
The color red has been shown to alter emotions, physiology, psychology, and behavior. Research has suggested that these alterations could possibly be due to a link between red and perceived dominance. In this study we examined if the color red is implicitly associated to the concept of dominance. In addition, we similarly hypothesized that blue is implicitly linked to rest. A modified Stroop word evaluation task was used in which 30 participants (23.07 ± 4.42 years) were asked to classify words shown in either red, blue, or gray (control condition), as being either dominant- or rest-related. The responses were recorded and analyzed for latency time and accuracy. The results revealed a significant word type × color interaction effect for both latency times, F(2,56) = 5.09, p = 0.009, ηp2 = 0.15, and accuracy, F(1.614,45.193) = 8.57, p = 0.001, ηp2 = 0.23. On average participants showed significantly shorter latency times and made less errors when categorizing dominance words shown in red, compared to blue and gray. The measured effects show strong evidence for an implicit red-dominance association and a partial red-rest disassociation. It is discussed that this association can possibly affect emotionality, with the presentation of red eliciting a dominant emotional and behavioral response.